Betacyanins from Gomphrena globosa L. flowers: Incorporation in cookies as natural colouring agents. (1st November 2020) - Roriz, Custódio Lobo; Heleno, Sandrina A.; Carocho, Márcio; Rodrigues, Paula; Pinela, José; Dias, Maria Inês; Fernandes, Isabel P.; Barreiro, Maria Filomena; Morales, Patricia; Barros, Lillian; Ferreira, Isabel C.F.R.
Highlights: Flowers of Gomphrena globosa L. were analyzed for their coloring capacity. The extracts were lyophilized or spray dried for stability analysis. Lyophilized and spray dried samples revealed high contents in betacyanins. Spray dried sample showed higher stability after incorporation in cookies. Incorporation maintained nutritional, physical and microbial profile of the cookies. Abstract: A betacyanin rich extract was obtained from the flowers of Gomphrena globosa L. by ultrasound-assisted extraction and dried either by lyophilization or spray-drying, was tested as a natural colourant in cookies and compared to a commercial colourant. The extracts were characterized in terms of betacyanin content and antioxidant potential. The effects of the colourants incorporation in the cookies were assessed through proximate composition, soluble sugars, fatty acids, color, texture and microbial load, over a shelf life of 30 days. Considering all the assays and analyzing the results through a 2-way analysis of variance, the cookies incorporated with spray-dried colourant showed the most intense pink coloration while cookies incorporated with lyophilized extract lost less color intensity over time. Thus, betacyanin extracts have potential as pink natural alternatives to synthetic colourants in the food industry.